2020
DOI: 10.3390/cancers12061560
|View full text |Cite
|
Sign up to set email alerts
|

New Use for Old Drugs: The Protective Effect of Risperidone on Colorectal Cancer

Abstract: (1) Background: The potential of old drugs in novel indications is being greatly valued. We propose a triple-model study involving population-based, cell, and animal studies to investigate the effects of risperidone, a type of second-generation antipsychotic (SGA) drug, on colorectal cancer. (2) Methods: We used data from Taiwan’s National Health Insurance Research Database between 1997 and 2013 to compare 101,989 patients with colorectal cancer and 101,989 controls. Conditional logistic regression analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Tumors were inoculated into the right flank of the mice, and treatment commenced when the average tumor size reached 80-100 mm 3 . On day 0, defined as the treatment initiation date, a single radiotherapy (11) session was administered, with adequate whole-body shielding to limit exposure to the tumor region only. Quetiapine, dissolved in 0.1% DMSO, was administered via gavage once daily.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors were inoculated into the right flank of the mice, and treatment commenced when the average tumor size reached 80-100 mm 3 . On day 0, defined as the treatment initiation date, a single radiotherapy (11) session was administered, with adequate whole-body shielding to limit exposure to the tumor region only. Quetiapine, dissolved in 0.1% DMSO, was administered via gavage once daily.…”
Section: Resultsmentioning
confidence: 99%
“…Progression in a Hep3B Xenograft Mouse Model carcinoma, gastric cancer, and colorectal cancer. It is important to note that the risk does not decrease for all cancers, as there are indications pointing to an elevated risk for breast cancer (8)(9)(10)(11)(12). Preclinical studies have also demonstrated that antipsychotics induce tumor suppression by promoting apoptosis, inhibiting cell cycle progression, downregulating the tumor microenvironment, and disrupting crucial signaling pathways involved in tumor growth, survival, angiogenesis, and metabolism (8,13).…”
Section: Quetiapine Significantly Improves the Effectiveness Of Radio...mentioning
confidence: 99%
“…However, administrative healthcare data are considered as alternative data sources if cancer registry data are unavailable or unfit for research purposes, especially in developing countries ( Valsecchi and Steliarova-Foucher, 2008 ; Abdul-Sater et al, 2021 ). Several previous studies have used administrative data to evaluate drug repurposing opportunities for cancers other than breast cancer ( Chen et al, 2019 ; Chen et al, 2020 ; Ng et al, 2021 ; Park et al, 2021 ). Some of these studies even have enriched administrative healthcare data ( Ng et al, 2021 ), or linkage to external registry to provide or confirm cancer-related clinical information ( Chen et al, 2019 ; Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have used administrative data to evaluate drug repurposing opportunities for cancers other than breast cancer ( Chen et al, 2019 ; Chen et al, 2020 ; Ng et al, 2021 ; Park et al, 2021 ). Some of these studies even have enriched administrative healthcare data ( Ng et al, 2021 ), or linkage to external registry to provide or confirm cancer-related clinical information ( Chen et al, 2019 ; Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Drug repurposing speeds up the overall development time and minimizes research expenses. Antipsychotic drugs such as olanzapine, risperidone and sertraline suppress tumor progress in several malignant disorders (10)(11)(12), which are expected to be a prospective reproposed antitumor drug. Unfortunately, there is no relevant study of such drugs in endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%